(untitled) (Indian Journal of Public Health Research & Development, 2021)
This cross-sectional study was undertaken to delineate the hygiene behavior among the female garment workers in Bangladesh during pre-COVID-19 period. 500 female garments workers were selected for the study. Data were collected by face-to-face interview method using semi-structured questionnaire which include the information on socio-demography, different components of personal hygiene such as bathing, brushing teeth, washing feet, washing/ changing cloth, washing hair by soap/ shampoo, trimming nail and washing hand. The majority of the participants (>75%) had ideal knowledge and practiceon every considered hygiene behavior. Regarding hand-washing behavior, only 3% had appropriate knowledge and ideally practiced by 60.2%. Knowledge of the respondents was significantly associated with ideal practice of all components (p=0.01). Predictors identified according to age, BMI, education and marital status of respondents, were significantly associated with hygiene related to bathing, washing feet, clothing, hair and hand.